Gene action and heterosis studies for yield and its components in upland rice - Kumar, Abhishek; Pandey, Deo Prakash (Journal of Cereal Research, 2024)
The present study was conducted to work out gene action and heterosis studies using Line × Tester mating design in rice using 10 lines suitable for rainfed upland conditions of H.P. and 3 testers in Kharif 2021 and 2022 (for crossing and evaluation, respectively). The per cent narrow sense heritability was low (